An integrated Linked Building Data system: AEC industry case. (February 2021) - Tchouanguem Djuedja, Justine Flore; Abanda, Fonbeyin Henry; Kamsu-Foguem, Bernard; Pauwels, Pieter; Magniont, Camille; Karray, Mohamed Hedi
Highlights: Data & information access & exchange using Linked Building Data (LBD) in Life Cycle. Resource Description Framework (RDF) graphs for a good application of semantic web. Layered Architecture - Application, Core, Application Programming Interface & Data. Integration of environmental data in a Building Information Modelling (BIM) tool. Ontology generation for the green construction promotion & sustainable development. Abstract: Environmental assessment is a critical activity for ensuring buildings are performing according to specified requirements, and efficient, seamless exchange of building information is crucial for environmental assessment. Therefore, all those involved in built environment issues should be able to access and share not only building information but also data about products, especially environmental assessment results for the products used in building projects. Of the several approaches that have been proposed to achieve efficient information exchange, semantic web technologies are amongst the most promising due to their capability to share data and enhance interoperability between the most heterogeneous systems. This study proposes an approach that can be used to make environmental data available in the early phases of the building lifecycle. It relies on Semantic Web techniques, especially Linked Data principles, while building on emerging Building Information Modelling (BIM) technology to propose an approach that facilitates information exchange to enhance the sustainability assessment of buildings. The paper ends with an illustration of how lifecycle inventory databases can be integrated, linked to BIM software and used in exchanging environmental building data.